Molecular Basis of Class A β-Lactamase Inhibition by Relebactam - Tooke, Catherine L.; Hinchliffe, Philip; Lang, Pauline A.; Mulholland, Adrian J.; Brem, Jürgen; Schofield, Christopher J.; Spencer, James (Antimicrobial agents and chemotherapy, 2019)
β-Lactamase production is the major β-lactam resistance mechanism in Gram-negative bacteria. β-Lactamase inhibitors (BLIs) efficacious against serine β-lactamase (SBL) producers, especially strains carrying the widely disseminated class A enzymes, are required. Relebactam, a diazabicyclooctane (DBO) BLI, is in phase 3 clinical trials in combination with imipenem for the treatment of infections by multidrug-resistant Enterobacteriaceae . β-Lactamase production is the major β-lactam resistance mechanism in Gram-negative bacteria. β-Lactamase inhibitors (BLIs) efficacious against serine β-lactamase (SBL) producers, especially strains carrying the widely disseminated class A enzymes, are required. Relebactam, a diazabicyclooctane (DBO) BLI, is in phase 3 clinical trials in combination with imipenem for the treatment of infections by multidrug-resistant Enterobacteriaceae . We show that relebactam inhibits five clinically important class A SBLs (despite their differing spectra of activity), representing both chromosomal and plasmid-borne enzymes, i.e., the extended-spectrum β-lactamases L2 (inhibition constant 3 μM) and CTX-M-15 (21 μM) and the carbapenemases KPC-2, -3, and -4 (1 to 5 μM). Against purified class A SBLs, relebactam is an inferior inhibitor compared with the clinically approved DBO avibactam (9- to 120-fold differences in half maximal inhibitory concentration [IC 50 ]). MIC assays indicate relebactam potentiates β-lactam (imipenem) activity against KPC-producing Klebsiella pneumoniae , with similar potency to avibactam (with ceftazidime). Relebactam is less effective than avibactam in combination with aztreonam against Stenotrophomonas maltophilia K279a. X-ray crystal structures of relebactam bound to CTX-M-15, L2, KPC-2, KPC-3, and KPC-4 reveal its C2-linked piperidine ring can sterically clash with Asn104 (CTX-M-15) or His/Trp105 (L2 and KPCs), rationalizing its poorer inhibition activity than that of avibactam, which has a smaller C2 carboxyamide group. Mass spectrometry and crystallographic data show slow, pH-dependent relebactam desulfation by KPC-2, -3, and -4. This comprehensive comparison of relebactam binding across five clinically important class A SBLs will inform the design of future DBOs, with the aim of improving clinical efficacy of BLI–β-lactam combinations.